2005
DOI: 10.1002/ajmg.a.30529
|View full text |Cite
|
Sign up to set email alerts
|

Nevo syndrome is allelic to the kyphoscoliotic type of the Ehlers–Danlos syndrome (EDS VIA)

Abstract: We report on seven patients affected with Nevo syndrome, a rare, autosomal recessive disorder characterized by increased perinatal length, kyphosis, muscular hypotonia, and joint laxity. Since its first description by Nevo et al. [1974], only a few cases have been reported. Because some of these patients present clinical features similar to those of the kyphoscoliotic type of Ehlers-Danlos syndrome (EDS VIA), an inherited connective tissue disorder characterized by a deficiency of lysyl hydroxylase due to muta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
49
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 14 publications
0
49
0
Order By: Relevance
“…In bone and other tissue collagens, 2 Hyl residues, 1 in each of 2 amino telopeptides or 2 carboxyl telopeptides, together with 1 Hyl or 1 Lys residue of the triple helix form the trivalent pyridinium cross-links hydroxylysyl pyridinoline (PYD) and lysyl pyridinoline (DPD), respectively. As a consequence, lysyl hydroxylase deficiency results in underhydroxylation of lysyl residues, an abnormal cross-link formation with consequent mechanical instability of the affected tissues, and an abnormal pattern of cross-links in urine, with a markedly increased DPD:PYD ratio 5.97 (0.99), range 4.3-8.1; n ϭ 17) (5,6 ). The diagnosis of this type of EDS can be confirmed by measurement of the activity of the enzyme in cultured skin fibroblasts and/or directly by mutation analysis of the procollagen-lysine 1, 2-oxoglutarate 5-dioxygenase 1 (PLOD1) gene, which encodes the lysyl hydroxylase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In bone and other tissue collagens, 2 Hyl residues, 1 in each of 2 amino telopeptides or 2 carboxyl telopeptides, together with 1 Hyl or 1 Lys residue of the triple helix form the trivalent pyridinium cross-links hydroxylysyl pyridinoline (PYD) and lysyl pyridinoline (DPD), respectively. As a consequence, lysyl hydroxylase deficiency results in underhydroxylation of lysyl residues, an abnormal cross-link formation with consequent mechanical instability of the affected tissues, and an abnormal pattern of cross-links in urine, with a markedly increased DPD:PYD ratio 5.97 (0.99), range 4.3-8.1; n ϭ 17) (5,6 ). The diagnosis of this type of EDS can be confirmed by measurement of the activity of the enzyme in cultured skin fibroblasts and/or directly by mutation analysis of the procollagen-lysine 1, 2-oxoglutarate 5-dioxygenase 1 (PLOD1) gene, which encodes the lysyl hydroxylase.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical markers of bone turnover are being investigated for their clinical utility in identifying osteoporotic fracture risk and determining and monitoring effective treatment for established disease. Also under investigation is the use of these markers as diagnostic tools for bone diseases other than osteoporosis, such as Paget disease and genetic disorders of collagen metabolism [e.g., the kyphoscoliotic form of Ehlers-Danlos syndrome (EDS) 4 (OMIM 225400) and its allelic entity Nevo syndrome (OMIM 601451)] ( [3][4][5][6].…”
mentioning
confidence: 99%
“…However, molecular study showed that Nevo syndrome and EDSVIA are, in fact, allelic. A founder mutation (Table 8) in the PLOD1 gene was found in these families [Guinta et al, 2005] [Al-Gazali, unpublished].…”
Section: Ehlers-danlos Syndrome Via (Edsvia)mentioning
confidence: 99%
“…This type of Ehlers-Danlos syndrome is classified as EDS type VI, which is also caused by a deficiency of lysyl-hydroxylase 1 (45,46). The clinical diagnosis of EDS type VI is characterized by severe muscle hypotonia at birth, progressive kyphoscoliosis, marked skin hyperelasticity with widened atrophic scars, and joint hypermobility (47,48). Interestingly, FKBP14 patients also displayed a wide spectrum of clinical features, such as myopathy, hearing loss, and aortic rupture (44).…”
mentioning
confidence: 99%